A Short Return to Simple Ah-Algebras with Real Rank Zero - Lin, Huaxin (MATHEMATICA SCANDINAVICA, 2014)
Let $A$ be a unital simple AH-algebra with stable rank one and real rank zero such that $kx=0$ for all $x\in\operatorname{ker}ρ_A$, the subgroup of infinitesmal elements in $K_0(A)$, and for the same integer $k\ge 1$. We show that $A$ has tracial rank zero and is isomorphic to a unital simple AH-algebra with no dimension growth.